ANALISIS WACANA KRITIS ATAS RELASI KUASA DALAM CERPEN “CORET-CORET DI TOILET KARYA EKA KURNIAWAN” MICHAEL FOUCAOLT - Nensilianti; Bungatang; Nhayla Zahra Annisa Muchlis Nhayla (Jurnal PENEROKA, 2026)
This study aims to analyze the power relations represented in the short story “Corat-Coret di Toilet” by Eka Kurniawan through Michel Foucault’s discourse perspective. The scope of this research focuses on discursive practices that demonstrate the mechanisms of power through the regulation of bodies, the formation of thought, and the emergence of forms of resistance in literary texts. The method used is descriptive qualitative with a critical discourse analysis approach based on Michel Foucault to examine the relationship between discourse, knowledge, and power. The research data consist of words, phrases, sentences, dialogues, and quotations from the short story “Corat-Coret di Toilet” that indicate discursive practices, social control, power relations, and forms of resistance against power. The findings reveal three main points: power relations over the body, power relations over thought, and resistance to power. Power relations over the body are identified through the father’s control over his daughter’s freedom in “Si Cantik yang Tak Boleh Keluar Malam,” whereas power relations over thought are seen in the university’s efforts to erase writings on toilet walls as a form of discourse control. An interesting fact from this study is that the toilet walls, often considered unimportant spaces, actually become alternative spaces for anonymous individuals to express criticism, ideas, and social unrest. These findings show that power operates not only through formal rules but also through discourse control, while resistance can emerge through discursive spaces that exist outside dominant power.